Optimized Quality of Color Image denoising using Convolution Neural Network - Sangita Minz (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
Optimized Quality of Color Image denoising using Convolution Neural Network